PENGETAHUAN IBU TENTANG PEMBERIAN MAKANAN PENDAMPING ASI PADA BAYI USIA DI ATAS 6 BULAN SAMPAI 24 BULAN DI DESA MUNCAN : MOTHER'S KNOWLEDGE ABOUT GIVING COMPLETE FOODS FOR BREAST MILK FOR BABIES OVER 6 MONTHS TO 24 MONTHS IN MUNCAN VILLAGE - Ismiati; Fuji Khairani; Leni Via Andini; Vera Yulandasari (Jurnal Kesehatan Qamarul Huda, 2023)
Complementary food for breast milk (MP-ASI) is food or drink that contains nutrients and is given to babies or children aged 6-24 months, to meet nutritional needs other than breast milk. MP-ASI is given according to the age of the toddler, namely MP-ASI for babies aged 6-9 months, MP-ASI for babies aged 9-12 months and MP-ASI for babies aged 12-24 months (Abeng & Hardiyanti, 2019). The aim of this research is to determine mothers' knowledge about providing complementary breast milk to babies aged over 6 months to 24 months in Muncan Village, Kopang District, Central Lombok Regency, in 2023. The research used in this research is a descriptive method. This research focused on finding out mothers' knowledge about giving MP-ASI to babies aged over 6 months to 24 months. The sample collection technique used purposive sampling. This research instrument uses a questionnaire. The results of research on maternal knowledge regarding giving complementary foods to breast milk for babies aged over 6 months to 24 months showed that 20 respondents (60.6%) had poor knowledge, followed by 8 respondents (24.2%) who had sufficient knowledge and 8 respondents (24.2%) who had good knowledge. 5 respondents (15.2%). Based on research conducted in Muncan Village, Kopang District, Central Lombok Regency, it was concluded that: 20 respondents (60.6%) had less knowledge about providing complementary breast milk (MP-ASI).